PALEOPROTEROZOIC GRANITES OF THE SHARYZHALGAI BLOCK, SIBERIAN CRATON PALEOMAGNETISM AND GEODYNAMIC INFERENCE - Didenko A.N.; Vodovozov V.Yu.; Kozakov I.K.; Khil'tova V.; Ivanov A.V.; Bibikova E.V.; Reznitskii L.Z.; Rasskazov S.V.; Levitskii V.I.; Travin A.V.; Shevchenko D.O. (My University, 2003)
Although the idea of the existence of a supercontinent that united the main ancient cratons in the Paleoproterozoic (1.9-1.7 Ga ago) has been debated over two decades, its configuration and position remain controversial. Several alternative reconstructions of the disposition of paleocontinents (in particular, the Siberian Craton) within the supercontinent are known. Concepts concerning the position of the Siberian Craton that have been put forward in publications are as follows: (1) the Arctic (herein, present-day coordinates) margin of the Siberian paleocontinent joined the western margin of Laurentia [2]; (2) Siberia and Laurentia were contiguous by their Arctic margins [2, 3]; and (3) the southern margin of Siberia came in contact with the Arctic margin of the Canadian Shield [4, 5]. These reconstructions are mainly based on interpretation of geological and isotopic-geochemical materials, while reliable paleomagnetic data are insufficient. However, only paleomagnetic data can delineate the position of blocks within the supercontinent. Qualitative paleomagnetic data, which are still absent, on Paleoproterozoic rocks of the Siberian Craton could help to solve this problem. The purpose of this work was to obtain such data.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская